The Relationship Of Mean Arterial Pressure (MAP) and Body Temperature With Outcome Of Glasgow Coma Scale (GCS) in Hemorrhagic Stroke Patients - suhron, M. (NHM PRESS, 2085)
Stroke is a circulatory disorders in the brain that causes impaired brain function. Theincrease in MAP and body temperature that occurs after stroke, suspected has correlationswith the result of bad outcome of GCS. The result of preliminary study showed that 6 (60%)from 10 respondents had a bad outcome of GCS, that was coma. The purpose of this studywas to analyze relationship of Mean Arterial Pressure (MAP) and body temperature withoutcome of Glasgow Coma Scale (GCS) in hemorrhagic stroke patients.This research design was analitic with approach of crosssectional. The independentvariables were MAP and body temperature. The dependent variable was outcome of GCS.The population in this research had 22 respondents. The samples taken were 21 respondents.The sampling used systematic random sampling. The instruments in this study wereobservations sheet and SOPs. The statistical test used Spearman Rank with Î± â‰¤ 0,05.The result of statistical test used Spearman Rank for relationship of MAP with outcomeof GCS obtained Pvalue of 0,045 so that the significance was smaller than the error level(0,045<0,05). While for relationship of body temperature with outcome of GCS obtainedPvalue of 0,000 so that the significance was smaller than the error level (0,000<0,05). Bothof them can be concluded that Ho was rejected and Ha was accepted so there wererelationship of MAP and body temperature with outcome of GCS in hemorrhagic strokepatients.Based on the result of the study, this study is expected to the power of nursing cansustain value of good MAP and body temperature for hemorrhagic stroke patients to preventbad outcome of GCS.